Assessment On Abandoned Housing Project: Impact and Revitalization in Malaysia - Salam, Saidah An'nisaa; Ariffin, Nur Farhayu; Ali, Mohamad Idris; Ramli, Noram Irwan (International Journal of Integrated Engineering, 2023)
The housing development sector was a key factor in the growth of Malaysia’s economic income since 1970s due to rapid urbanization. Unfortunately, housing construction in Malaysia still facing the abandonment issues due to financial constraints and many other factors. Abandoned housing project give a huge impact to the environment and socio economic to the stakeholder involved directly or indirectly. The purpose of this study is to overview the impact of abandoned housing project and to study the best solution in preventing the issues. Extensive literature review has been done to find out the actual scenario and impact of abandoned housing project issue. The questionnaire survey has been done to investigate the best solution in preventing and minimize the problem of abandoned housing project. The abandoned housing project give an impact to all parties and the proper financial management, amend the development concept, study the market signal properly, amend the initial policy of housing development and finally takeover the problematic development by the government is the best solution in preventing it.